An induction principle for spectral and rearrangement inequalitities
An induction principle for spectral and rearrangement inequalitities
In this paper, expressions of the form <inline-formula content-type="math/mathml"> <mml:math xmlns:mml="http://www.w3.org/1998/Math/MathML" alttext="f precedes g"> <mml:semantics> <mml:mrow> <mml:mi>f</mml:mi> <mml:mo>≺<!-- ≺ --></mml:mo> <mml:mi>g</mml:mi> </mml:mrow> <mml:annotation encoding="application/x-tex">f \prec g</mml:annotation> </mml:semantics> </mml:math> </inline-formula> or <inline-formula content-type="math/mathml"> <mml:math xmlns:mml="http://www.w3.org/1998/Math/MathML" alttext="f precedes precedes g"> <mml:semantics> <mml:mrow> <mml:mi>f</mml:mi> <mml:mo>≺<!-- ≺ -->≺<!-- ≺ --></mml:mo> <mml:mi>g</mml:mi> </mml:mrow> <mml:annotation encoding="application/x-tex">f …